A challenging playing field: Identifying the endogenous impediments to annulus fibrosus repair. Issue 1 (11th February 2021) - Peredo, Ana P.; Gullbrand, Sarah E.; Mauck, Robert L.; Smith, Harvey E.
Abstract: Intervertebral disc (IVD) herniations, caused by annulus fibrosus (AF) tears that enable disc tissue extrusion beyond the disc space, are very prevalent, especially among adults in the third to fifth decade of life. Symptomatic herniations, in which the extruded tissue compresses surrounding nerves, are characterized by back pain, numbness, and tingling and can cause extreme physical disability. Patients whose symptoms persist after nonoperative intervention may undergo surgical removal of the herniated tissue via microdiscectomy surgery. The AF, however, which has a poor endogenous healing ability, is left unrepaired increasing the risk for re‐herniation and pre‐disposing the IVD to degenerative disc disease. The lack of understanding of the mechanisms involved in native AF repair limits the design of repair systems that overcome the impediments to successful AF restoration. Moreover, the complexity of the AF structure and the challenging anatomy of the repair environment represents a significant challenge for the design of new repair devices. While progress has been made towards the development of an effective AF repair technique, these methods have yet to demonstrate long‐term repair and recovery of IVD biomechanics. In this review, the limitations of endogenous AF healing are discussed and key cellular events and factors involved are highlighted to identify potential therapeutic targets that can be integrated into AF repair methods. Clinical repair strategies and their limitations are described to further guide the design of repair approaches that effectively restore native tissue structure and function.